Chemical stability and electrochemical characteristics of FeS microcrystals as the cathode material of rechargeable lithium batteries1. Issue 23 (21st June 2015) - Tran, Dat T.; Zhang, Sheng S.
<x xml:space="preserve">Abstract</x> Recharging of a fully discharged Li/FeS battery does not reconstitute the original FeS structure; further cycling is co-contributed by the Li2S/Li2Sn and Fe/FeS redox couples and affected by the electrolyte solvent and charging cutoff voltage.